Reverse Genetics of RNA Viruses Applications and Perspectives - Bridgen, Anne (Wiley, 2012)
Reverse genetics, the genetic manipulation of RNA viruses to create a wild-type or modified virus, has led to important advances in our understanding of viral gene function and interaction with host cells. Since many severe viral human and animal pathogens are RNA viruses, including those responsible for polio, measles, rotaviral diarrhoea  and influenza infections, it is also an extremely powerful technique with important potential application for the prevention and control of a range of human and animal viral diseases. Reverse Genetics of RNA Viruses provides a comprehensive account of the very latest developments in reverse genetics of RNA viruses through a wide range of applications within each of the core virus groups including; positive sense, negative sense and double stranded RNA viruses. Written by a team of international experts in the field, it provides a unique insight into how the field has developed, what problems are being addressed now and where applications may lead in the future. It will prove invaluable to bioscience, medical and veterinary students, those starting research in this area as well as other researchers and teachers needing to update their knowledge of this fast-moving field. An authoritative, comprehensive overview of reverse genetics in RNA Viruses. Includes numerous examples of cutting- edge applications of reverse genetics within each of the RNA viral groups.  Written by a team of international experts, including some of the leading researchers in the field